2022
DOI: 10.1158/1538-7445.sabcs21-p5-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-13-14: Antitumor activity of patritumab deruxtecan (HER3-DXd), a HER3-directed antibody drug conjugate (ADC) across a diverse panel of breast cancer (BC) patient-derived xenografts (PDXs)

Abstract: Background: HER3 is overexpressed in 30-50% of breast cancers and has been associated with poor prognosis. Patritumab deruxtecan (HER3-DXd; U3-1402) is a HER3-directed ADC with a potent topoisomerase I (TOP1) inhibitor payload. A phase 1/2 study of HER3-DXd (NCT02980341) demonstrated promising antitumor activity in hormone receptor positive (HR+) metastatic BC patients with clinical activity observed across baseline levels of HER3 protein or mRNA expression. A window of opportunity clinical trial is currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[6][7][8][9] In HER3-expressing xenograft models, HER3-DXd demonstrated antitumor responses across a range of baseline HER3 expression levels 10,11 that were sustained over time. 11 Moreover, in vitro studies have shown that HER3-DXd inhibits the proliferation of chemotherapyresistant breast cancer cell lines with upregulated baseline HER3 expression. 12 U31402-A-J101 (ClinicalTrials.gov identifier: NCT02980341) is assessing the safety and efficacy of HER3-DXd in patients with HER3-expressing advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] In HER3-expressing xenograft models, HER3-DXd demonstrated antitumor responses across a range of baseline HER3 expression levels 10,11 that were sustained over time. 11 Moreover, in vitro studies have shown that HER3-DXd inhibits the proliferation of chemotherapyresistant breast cancer cell lines with upregulated baseline HER3 expression. 12 U31402-A-J101 (ClinicalTrials.gov identifier: NCT02980341) is assessing the safety and efficacy of HER3-DXd in patients with HER3-expressing advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Patritumab deruxtecan (U3-1402; HER3-DXd) is a novel, first-in-class, HER3-directed antibody-drug conjugate (ADC) that is composed of a human immunoglobulin G1 monoclonal antibody to HER3 (patritumab) covalently bonded to an exatecan-derived topoisomerase I inhibitor payload via a stable, tetrapeptide-based, tumor-selective, cleavable linker. 6 - 9 In HER3-expressing xenograft models, HER3-DXd demonstrated antitumor responses across a range of baseline HER3 expression levels 10 , 11 that were sustained over time. 11 Moreover, in vitro studies have shown that HER3-DXd inhibits the proliferation of chemotherapy-resistant breast cancer cell lines with upregulated baseline HER3 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation